PENGARUH KEPEMILIKAN INSTITUSIONAL, PROPORSI DEWAN KOMISARIS INDEPENDEN, KOMITE AUDIT, PERTUMBUHAN PENJUALAN DAN LEVERAGE TERHADAP TAX AVOIDANCE - Windarni, Nunung; Nurlaela, Siti; ., Suhendro (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan; Vol 1 No 1 (2018): Prosiding Seminar Nasional dan Call for Papers Manajemen, Akuntansi, dan Perbankan 2018, 2018)
This study aims to obtain empirical evidence to know the effect of institutional ownership, the proportion of independent commissioners, audit committees, sales growth and leverage to tax avoidance. The independent variables in this study are institutional ownership, proportion of board of commissioners, audit committee, sales growth and leverage. The dependent variable in this research is tax avoidance using Cash Effective Tax Rate (CETR). The data in this research is secondary data obtained from Indonesia Stock Exchange. The sample amount of 16 companies from the basic industry sector for the period of 2013-2017, using purposive sampling method. Data analysis technique used linear logistic regression, data processed by using SPSS 24. The result of the analysis shows that the proportion of independent commissioners influences tax avoidance, then institutional ownership, proportion of board of commissioner, audit committee, sales growth, and leverage have no effect to tax advoidance.